Differences in growth between offspring of anadromous and freshwater brown trout Salmo trutta. Issue 1 (25th February 2021) - Jonsson, Bror; Jonsson, Nina
Abstract: In this study, individual growth of juvenile offspring of anadromous and freshwater resident brown trout Salmo trutta and crosses between the two from the River Imsa, Norway, was estimated. The juveniles were incubated until hatching at two temperatures (±S.D. ), either 4.4 ± 1.5°C or 7.1 ± 0.6°C. Growth rate was estimated for 22 days in August–September when the fish on average were c . 8 g in wet mass, and the estimates were standardized to 1 g fish dry mass. Offspring of anadromous S. trutta grew better at both 15 and 18°C than offspring of freshwater resident S. trutta or offspring of crosses between the two S. trutta types. This difference appears not to result from a maternal effect because anadromous S. trutta grew better than the hybrids with anadromous mothers. Instead, this appears to be an inherited difference between the anadromous and the freshwater resident fish lending support to the hypothesis that anadromous and freshwater resident S. trutta in this river differ in genetic expression. Egg incubation temperature of S. trutta appeared not to influence the later growth as reported earlier from the studies of Atlantic salmon Salmo salar .